Optimizing of Counterfort Retaining Wall with Varying Heights - Chua, Guang Seng; Koh, Heng Boon (Recent Trends in Civil Engineering and Built Environment, 2025)
Retaining wall is generally classified as geotechnical structures that used for retaining soil and resisting lateral earth pressure. The ability of cantilever retaining wall or gravity wall to resist the backfill have a height limitation up to 6m. This paper presents the outcomes of the analysis and design of counterfort retaining wall ranging from 8m to 12m. The counterfort retaining wall was subjected to the lateral earth pressure due to granular material and a surcharge loading of 10 kN/m2. Due to complexity of the counterfort retaining wall, member forces of counterfort retaining wall were determined based on the analysis from StaadPro software. The structure elements of the counterfort retaining wall were designed based on Eurocode 2. An Excel spreadsheet was developed to conduct the repetitive design and calculation for structural members design. In general, the bending moments for short span and long span at stem and base are increase linearly as the height of counterfort retaining wall increase. From the data analysis, the support moments always greater than the midspan moments for both short and long spans of stem and base. A series of standard design tables with detailing were produced. The standard design tables serve as a quick reference for the engineers in selecting appropriate dimensions and reinforcement for counterfort retaining wall based on the desired concrete grade.